河北省国有林场二三产业经济效益分析 = A study on synergy of forestry attached enterprises - 白顺江 Bai, Shun Jiang (2008)
The enterprises run by forestry farms have developed to such a degree that their contribution has become an important source of income of the forestry farms. Especially in nowadays, since people are becoming more and more concerned to the issue of ecological and environmental preservation, it has become more important to protect and develop the forest through the development of enterprises run by the forestry farms. However, in the last 20 years, the forestry farms took quite a lot of roundabout courses in the aspect of developing enterprises. Influenced by the idea of "making the appraisal of forestry not only from the view of a forestry man, developing the forestry not only through the work in the field of forestry", some forestry farms carried out lots of enterprise projects not related to the advantages of themselves. Failure of these projects has induced huge waste of resources.